2014
DOI: 10.1073/pnas.1406297111
|View full text |Cite
|
Sign up to set email alerts
|

Direct phase-sensitive identification of a d -form factor density wave in underdoped cuprates

Abstract: The identity of the fundamental broken symmetry (if any) in the underdoped cuprates is unresolved. However, evidence has been accumulating that this state may be an unconventional density wave. Here we carry out site-specific measurements within each CuO 2 unit cell, segregating the results into three separate electronic structure images containing only the Cu sites [Cu(r)] and only the x/y axis O sites [O x (r) and O y (r)]. Phase-resolved Fourier analysis reveals directly that the modulations in the O x (r)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
260
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 226 publications
(300 citation statements)
references
References 46 publications
35
260
2
2
Order By: Relevance
“…The earlier muon spin relaxation results 26,27 , together with the ED measurements, allow us to rule out the existing proposals of SDW formation 32,33 or a phonon-driven CDW 34 . Instead, an intra-unit-cell charge-nematic electronic symmetry breaking is implicated, similar to that proposed for doped cuprates 39 .…”
Section: Discussionsupporting
confidence: 61%
“…The earlier muon spin relaxation results 26,27 , together with the ED measurements, allow us to rule out the existing proposals of SDW formation 32,33 or a phonon-driven CDW 34 . Instead, an intra-unit-cell charge-nematic electronic symmetry breaking is implicated, similar to that proposed for doped cuprates 39 .…”
Section: Discussionsupporting
confidence: 61%
“…Within a given "hot region" in the Brillouin zone, the spin-fluctuation exchange gives rise to CDW order with a small momentum, much like as the one due to small-Q phonon exchange 28 , Magnetically mediated CDW order also naturally gives rise to a sign change between CDW orders in different hot regions separated by (π, π). This is consistent with the observed d-wave formfactor of the CDW order parameter 11 .…”
Section: Introductionsupporting
confidence: 91%
“…An incommensurate CDW order has been observed in La-based cuprates a while ago 1,2 , and recently was found to be ubiquitous in the cuprates [3][4][5][6][7][8][9][10][11][12][13] . The CDW order is incommensurate, with momentum Q along X and/or Y directions, where Q ∼ (0.2 − 0.3) × 2π.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Achkar et al 14 have reported resonant soft x-ray scattering measurements which show that the charge distribution on the oxygens of LBCO have an s -CDW orbital structure in which the charge modulations on the O px and O py sites in a unit cell are in phase. STM Studies of BSCCO (p ∼ 8%) and NaCCOC (p ∼ 12%) find that these materials have a predominantly d-CDW orbital form factor in which these O px and O py charge modulations are out of phase 15 . Finally, recent resonant x-ray scattering measurements of Nd 2−x Ce x CuO 4 near optimal doping 16 find charge order which occurs with a similar periodicity and Cu-O bond orientation to that of the charge stripes seen in LBCO.…”
mentioning
confidence: 99%